Commodity price volatility and risk in supply chains - Zsidisin, George A. (Henry Stewart Talks, 2014)
Importance of commodity price risk management, Assessing price risk exposure, Degree of price volatility, Risk tolerance and objectives, Technical analysis, Gathering price data, Identifying price patterns, Selecting and developing short term forecasts, Improving short term forecasts, Fundamental analysis, Gather market and price data, Understanding supply, Understanding demand, Using correlation and regression to forecast long term prices, Monitoring changes and adjusting long term forecasts, Creating a commodity price risk management strategy, Substituting commodities, Passing and sharing price risk, Forward buying, Hedging and cross-hedging, Absorbing price risk and reducing demand